2019
DOI: 10.1002/pmic.201900004
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Quantitative Proteomics of Enriched Nuclei from Sugarcane (Saccharum ssp) Stems in Response to Drought Stress

Abstract: Drought is considered the major abiotic stress limiting crop productivity. This study seeks to identify proteins involved in the drought response in sugarcane stems submitted to drought stress. The integration of nuclei enrichment sample preparation with the shotgun proteomic approach results in great coverage of the sugarcane stem proteome with 5381 protein groups identified. A total of 1204 differentially accumulated proteins are detected in response to drought, among which 586 and 618 are increased and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…We found several genes potentially related to drought tolerance that had deletions unique to cluster 1, which is particularly interesting given that cluster 1 is comprised almost entirely of genotypes from Ethiopia. These drought tolerance genes included Sobic.004G042400, a Myb/SANT-like DNA-binding domain protein that showed differential abundance in response to drought in sugarcane ( Salvato et al 2019 ), Sobic.004G183600, a molybdenum cofactor biosynthesis protein whose overexpression was found to confer increased drought tolerance in maize ( Lu et al 2013 ), and Sobic.008G100400, a member of the pentatricopeptide repeat family with critical roles in stress and development in many plant species ( Sharma and Pandey 2015 ). Two genes with cluster 1 specific deletions had putative roles in both drought and salt tolerance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found several genes potentially related to drought tolerance that had deletions unique to cluster 1, which is particularly interesting given that cluster 1 is comprised almost entirely of genotypes from Ethiopia. These drought tolerance genes included Sobic.004G042400, a Myb/SANT-like DNA-binding domain protein that showed differential abundance in response to drought in sugarcane ( Salvato et al 2019 ), Sobic.004G183600, a molybdenum cofactor biosynthesis protein whose overexpression was found to confer increased drought tolerance in maize ( Lu et al 2013 ), and Sobic.008G100400, a member of the pentatricopeptide repeat family with critical roles in stress and development in many plant species ( Sharma and Pandey 2015 ). Two genes with cluster 1 specific deletions had putative roles in both drought and salt tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 1 had the most cluster-specific deletions related to drought tolerance. The size of these mutations ranged from an 80 bp deletion in a molybdenum cofactor biosynthesis protein 1 to a 3.6 kbp deletion in a Myb/SANT-like DNA-binding domain-containing protein, two genes that have been found to be differentially expressed in response to drought in maize and sugarcane respectively ( Lu et al 2013 ; Salvato et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…While maize and tomato plants showed a reduction of amino acids content when exposed to N deficiency (i.e., Trp, Arg, Asp), different accessions of Arabidopsis had an increase of the levels of some amino acids (glycine -Gly, histidine -His, leucine -Leu, Ile). This response was explained as an ability for adjusting the amino acids to compensate the decrease of N availability, mainly through an increased protein degradation (Bassi et al 2018;Fritz et al 2006;Salvato et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Their results revealed that the expression of fructose-bisphosphate aldolase, oxygen-evolving enhancer protein, and SOD were elevated in two or three organs of K86-161, whereas these proteins decreased in B34-164 under drought stress. More recently, Salvato et al [93] carried out quantitative proteomics of enriched nuclei from sugarcane ( Saccharum ssp) stems in response to drought stress by filter-aided sample preparation (FASP) and LC–MS/MS. The results show that most of 74 exclusives proteins of control plants are related to cell wall metabolism, suggesting that drought affects negatively the cell wall metabolism; Also, 37 TFs that were associated to protein domains, such as leucine-rich (bZIP), C2H2, NAC, C3H, LIM, Myb-related, heat shock factor (HSF) and auxin response factor (ARF), are identified.…”
Section: Sugarcane Proteomicsmentioning
confidence: 99%
“…The results show that most of 74 exclusives proteins of control plants are related to cell wall metabolism, suggesting that drought affects negatively the cell wall metabolism; Also, 37 TFs that were associated to protein domains, such as leucine-rich (bZIP), C2H2, NAC, C3H, LIM, Myb-related, heat shock factor (HSF) and auxin response factor (ARF), are identified. These TFs belong to low abundant nuclear proteins and are differentially accumulated in response to drought stress [93].…”
Section: Sugarcane Proteomicsmentioning
confidence: 99%